COST ACCOUNTANT AND INDUSTRIAL ENGINEER. - Latzer, Paul J. (The Accounting Review, 1955)
Cost accountant and industrial engineer, both professions work side by side, gathering and analyzing manufacturing cost data. The disinterest of the cost accountant in the work of his engineering colleague is not at all reciprocated by the latter. The reason is that the curricula of industrial engineering schools include study of the principles of both general and cost accounting, so that the engineering graduate is fairly well versed in costing principles from every angle. As a rule, the services of the cost accountant are properly considered indispensable in the keeping of records, distribution of overhead, allocation of costs to jobs or processes, and so on, and the smaller manufacturer is more likely to have on his payroll a cost accountant than an industrial engineer. Under the circumstances, the accountant who is not familiar with atleast the principal procedures of the time-study analyst may find he has become a sort of glorified clerk, unable to furnish his employer vital cost data.